STUDI BLOCKAGE EFFECT TERHADAP ALIRAN PADA KONFIGURASI WING-BODY FAIRING - Khoiri Rozi; Herman Sasongko (Mesin, 2008)
The study was performed to acquire information on the qualitative flow condition and dynamical blockage effect on wing-body fairing configuration. The study was used to computational fluid dynamics to provide the pathlines patters and the total static pressure distribution in the vicinity junction region. Results of study in the research indicated that flow pattern influences by variation of angle of attack. As increasing of angle of attct so that the saddle point position move in to pressure side and away from wing surface. Meanwhile, separation line or imprint horseshoe vortex due to increasing angle of attack became more than opened. Results of total static pressure distribution show that the blockafe effect area seems deeply on incoming trailing edge location. Therefore, as increasing of angle of attack will be blockage effect to fluid flow on pressure side and suction side stronger.